Unique vesicular nano‐architecture of thiobarbiturate derived chitosan with excellent hydrophilicity. Issue 1 (1st November 2021) - Mandal, Piyali; Mukherjee, Madhumita; Patra, Diptendu; Shunmugam, Raja
Abstract: The natural polymer chitosan is conjugated with hydrophilic thiobarbiturate entity which makes the whole molecule amphiphilic as well as water‐soluble. The water solubility of this molecule leads to an interesting supramolecular architecture via self‐assembly. The monomers are synthesized via Friedel Crafts alkylation and ring‐closing reaction where homopolymers derivatives undergo coupling and thiol‐ene click reaction. The monomer and the modified polymers are well characterized through conventional spectroscopic techniques. The self‐assembly behavior is then confirmed through critical aggregation concentration study and dynamic light scattering. The field emission scanning electron microscope and transmission electron microscope images provide the architectures' fascinating morphology. Finally, the loading and release of doxorubicin drug are performed to investigate the biomedical applications. Abstract :